Medaka as model animal and current status of medaka biological resources - Naruse, Kiyoshi; Chisada, Shinichi; Sasado, Takao; Takehana, Yusuke (Food Agricultural Sciences and Technology, 2016)
The medaka species is used as a model animal throughout the world. As an experimental animal, it is similar to zebrafi sh but has important distinguishing features. As it lives in the temperate zone, medaka spawning is infl uenced by photoperiods and circadian rhythms. Medaka can adapt to lower temperatures in winter and higher temperatures in summer. Adaptation to high salinity has also been observed. Medaka research has been supported by important biological resources hosted by the National Bio-Resource Project (NBRP) since 2002. NBRP Medaka is a central repository of medaka resources that provides the research community with fi sh, cDNA/BAC/fosmid materials, hatching enzyme, useful databases and, more recently, a TILLING library for mutant screening and a genome editing platform based on CRISPR-Cas9. NBRP Medaka continues to support the medaka research community by enhancing productivity, continuity and reproducibility.